2015
DOI: 10.1111/1348-0421.12260
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of semi‐solid medium in the isolation of highly virulent Leptospira strains from wild rats in an urban area of Fukuoka, Japan

Abstract: Leptospirosis is a worldwide zoonosis. The importance of urban leptospirosis is recognized in Japan: urban rats carry pathogenic leptospires and people acquire these pathogens through contact with surface water or soil contaminated by the urine of the infected animals. To determine the current Leptospira carriage rate in urban rats, 29 wild rats were trapped in the central area of Fukuoka and strains isolated from their kidneys and urine analyzed. When semi-solid Korthof's medium containing 0.1% agar was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, there are only a few reports describing the isolation of virulent Leptospira from environmental samples; as discussed above, the main difficulty in the isolation of these species is the overgrowth of environmental bacteria or the fast-growing saprophytic Leptospira (Barragan et al, 2011;Benacer et al, 2013;Saito et al, 2013). Culture-based protocols include the use EMJH (Ellinghausen and McCullough modified by Johnson and Harris) culture medium containing cocktails of antibacterial and anti-fungal compounds such as sulfamethoxazole, trimethoprim, amphotericin B, fosfomycin, and 5-fluorouracil (Benacer et al, 2013;Saito et al, 2015;Saito et al, 2013). Alternatively bacterial contamination in water samples can be reduced by utilizing 0.22 µm filtrate before enriching in EMJH medium, then isolating colonies on solid medium (Saito et al, 2015;Wuthiekanun et al, 2013 Kumar et al, 2016b;Aviat et al, 2010) or pathogenic specific sequences of genes, such as flaB (Villanueva et al, 2014), secY (Perez and Goarant, 2010;Guernier et al, 2018) and the 16S rRNA gene (Ganoza et al, 2006).…”
Section: Culture From Environmental Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are only a few reports describing the isolation of virulent Leptospira from environmental samples; as discussed above, the main difficulty in the isolation of these species is the overgrowth of environmental bacteria or the fast-growing saprophytic Leptospira (Barragan et al, 2011;Benacer et al, 2013;Saito et al, 2013). Culture-based protocols include the use EMJH (Ellinghausen and McCullough modified by Johnson and Harris) culture medium containing cocktails of antibacterial and anti-fungal compounds such as sulfamethoxazole, trimethoprim, amphotericin B, fosfomycin, and 5-fluorouracil (Benacer et al, 2013;Saito et al, 2015;Saito et al, 2013). Alternatively bacterial contamination in water samples can be reduced by utilizing 0.22 µm filtrate before enriching in EMJH medium, then isolating colonies on solid medium (Saito et al, 2015;Wuthiekanun et al, 2013 Kumar et al, 2016b;Aviat et al, 2010) or pathogenic specific sequences of genes, such as flaB (Villanueva et al, 2014), secY (Perez and Goarant, 2010;Guernier et al, 2018) and the 16S rRNA gene (Ganoza et al, 2006).…”
Section: Culture From Environmental Samplesmentioning
confidence: 99%
“…Culture-based protocols include the use EMJH (Ellinghausen and McCullough modified by Johnson and Harris) culture medium containing cocktails of antibacterial and anti-fungal compounds such as sulfamethoxazole, trimethoprim, amphotericin B, fosfomycin, and 5-fluorouracil (Benacer et al, 2013;Saito et al, 2015;Saito et al, 2013). Alternatively bacterial contamination in water samples can be reduced by utilizing 0.22 µm filtrate before enriching in EMJH medium, then isolating colonies on solid medium (Saito et al, 2015;Wuthiekanun et al, 2013 Kumar et al, 2016b;Aviat et al, 2010) or pathogenic specific sequences of genes, such as flaB (Villanueva et al, 2014), secY (Perez and Goarant, 2010;Guernier et al, 2018) and the 16S rRNA gene (Ganoza et al, 2006). Because of sequence polymorphisms, PCR targeting lipL32 or secY fail to detect virulent Leptospira of the intermediate cluster (e.g.…”
Section: Culture From Environmental Samplesmentioning
confidence: 99%
“…Another bacterial gene that is widely used in phylogenetic studies is the gyrB gene, which is reported to have a higher nucleotide divergence in Leptospira species than the 16S RNA rrs gene (Huang, 1996; Slack et al , 2006). This gene target has also been used for Leptospira diagnostic assays (Slack et al , 2006) and typing of isolates carried by rodents in Japan and the Philippines (Kawabata et al , 2006; Saito et al , 2015; Villanueva et al , 2014).…”
Section: Leptospira Barcoding: Targets and Databasesmentioning
confidence: 99%